Lactobacillus delbrueckii Interfere With Bile Acid Enterohepatic Circulation to Regulate Cholesterol Metabolism of Growing–Finishing Pigs via Its Bile Salt Hydrolase Activity - Hou, Gaifeng; Peng, Wei; Wei, Liangkai; Li, Rui; Yuan, Yong; Huang, Xingguo; Yin, Yulong (Frontiers in Nutrition, 2020)
Microbiota-targeted therapies for hypercholesterolemia get more and more attention and is recognized as an effective strategies for preventing and treating cardiovascular disease (CVD). The experiment was conducted to investage the cholesterol-lowering mechanism of Lactobacillus delbrueckii in a pig model. Twelve barrows (38.70 ± 5.33 kg) were randomly allocated to 2 groups and fed corn-soybean meal diets with either 0 (Con) or 0.1 % Lactobacillus delbrueckii (Con + LD) for 28 days. Lactobacillus delbrueckii-fed pigs had lower serum contents of total cholesterol (TC), total bile acids (TBA) and triglyceride (TG), but higher fecal TC and TBA excretion. Lactobacillus delbrueckii treatment increased ileal Lactobacillus abundance and BA deconjugation and affected serum and hepatic BA composition. Dietary Lactobacillus delbrueckii downregulated the gene expression of ileal apical sodium-dependent bile acid transporter (ASBT) and ileal bile acid binding protein (IBABP), and hepatic farnesoid X receptor (FXR), fibroblast growth factor (FGF19) and small heterodimer partner (SHP), but upregulated hepatic high density lipoprotein receptor (HDLR), low density lipoprotein receptor (LDLR), sterol regulatory element binding protein-2 (SREBP-2) and cholesterol-7α hydroxylase (CYP7A1) expression. Our results provided in vivo evidences that Lactobacillus delbrueckii promote ileal BA deconjugation with subsequent fecal TC and TBA extraction by modificating ileal microbiota composition and induce hepatic BA neosynthesis via regulating gut-liver FXR-FGF19 axis.